Refined Method for Choosing a Security Solution for Mobile Application – Web Service Interactions - Trif, Silvia; Visoiu, Adrian (Journal of Mobile, Embedded and Distributed Systems, 2011)
This paper aims to present a refined algorithm for choosing the appropriate security implementation for mobile applications connecting to web services. Common security scenarios are presented. Each scenario has several characteristics associated. The correlations between these security scenarios characteristics are computed and selected only the characteristics that are less correlated. The proposed algorithm inventories the available scenarios, inventories the requirements and selects the security scenario that match. A case study applies the proposed method to a situation where a WP7 application and a WCF service are interacting. Security scenarios for WCF services and their characteristics are described. Application security requirements are established. A security solution is proposed based on the results of the proposed method.